2019
DOI: 10.1111/crj.13049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pulmonary hypertension patients living in plain and high‐altitude regions

Abstract: Objective The demographic characteristics, ratio of aetiologies and biochemical parameters of adult patients with pulmonary hypertension (PH) living in plain and high‐altitude regions were investigated and analysed. Methods In total, 2846 adult patients with PH hospitalized from 2010 to 2015 in the Second Xiangya Hospital of Central South University and Qinghai Red Cross Hospital were retrospectively investigated. Results (1) In the present study, the numbers of patients with PH in both the plain and high‐alti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A recent study retrospectively analyzed etiologies of pulmonary hypertension in patients admitted over five years to the Qinghai Red Cross Hospital, located at 2200 m [289]. Interestingly, in high altitude dwellers, various clinical forms of pulmonary hypertension from clinical group 1 to 5 were diagnosed [289]. The analysis showed that the most common form was pulmonary hypertension due to lung diseases [289].…”
Section: Other Clinical Forms Of Pulmonary Hypertension At High Altitudementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study retrospectively analyzed etiologies of pulmonary hypertension in patients admitted over five years to the Qinghai Red Cross Hospital, located at 2200 m [289]. Interestingly, in high altitude dwellers, various clinical forms of pulmonary hypertension from clinical group 1 to 5 were diagnosed [289]. The analysis showed that the most common form was pulmonary hypertension due to lung diseases [289].…”
Section: Other Clinical Forms Of Pulmonary Hypertension At High Altitudementioning
confidence: 99%
“…Interestingly, in high altitude dwellers, various clinical forms of pulmonary hypertension from clinical group 1 to 5 were diagnosed [289]. The analysis showed that the most common form was pulmonary hypertension due to lung diseases [289]. Pulmonary hypertension due to chronic lung disease is also common in Andean highlanders [290].…”
Section: Other Clinical Forms Of Pulmonary Hypertension At High Altitudementioning
confidence: 99%
“…The physiological response of the pulmonary circulation to hypoxia is to increase pulmonary arteriolar resistance, resulting in elevated pulmonary artery pressure (ePAP) (1)(2)(3)(4)(5)(6). Various degrees of increases in PAP at high altitudes have been reported in recent decades (3,(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological response of the pulmonary circulation to hypoxia is to increase pulmonary arteriolar resistance, resulting in elevated pulmonary artery pressure (ePAP) (1)(2)(3)(4)(5)(6). Various degrees of increases in PAP at high altitudes have been reported in recent decades (3,(5)(6)(7)(8)(9)(10). However, excessive ePAP in response to high-altitude hypoxia is a critical physiopathological factor in hypoxic adaptation leading to high-altitude pulmonary edema in the acute phase or high-altitude pulmonary hypertension (PH) in the long term (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a resting mean pulmonary artery pressure of 25 mm Hg or above are diagnosed as pulmonary hypertension (PH), which is divided into five groups in clinic. 1,2 Pulmonary arterial hypertension (PAH) is one type of PH, featured with vasoconstriction obstructed pulmonary vasculature, adverse vascular remodelling, vascular fibrosis and stiffening structure. In the past decades, improved understanding of the pathophysiology of PAH leads to the development of efficient clinical drugs targeting vascular remodelling.…”
Section: Introductionmentioning
confidence: 99%